Diagnostic accuracy of a mutation-specific monoclonal antibody (RM8 clone) for BRAF V600e detection by immunohistochemistry in ameloblastomas - Martins-de-Barros, Allan Vinícius; Araújo, Fábio Andrey da Costa; Barros, Ana Maria Ipólito; Lazo, Raisa Jordana Geraldine Severino; Barbosa Neto, Adauto Gomes; Silva, Helker Albuquerque Macedo da; Muniz, Maria Tereza Cartaxo; Ferreira, Stefânia Jeronimo; Carvalho, Marianne de Vasconcelos (Journal of Oral Diagnosis, 2025)
Objective: To determine the diagnostic accuracy of IHC using anti-BRAF V600E monoclonal antibody (RM8 clone) compared to Real-Time PCR in the detection of BRAF V600E mutation in FFPE ameloblastoma samples. Methods: This is a diagnostic accuracy study conducted based on the STARD recommendations. The index test was the IHC with anti-BRAF V600E antibody (RM8 clone), while the reference standard was the DNA analysis through castPCR™ mutation detection assays. The target condition was the detection of BRAF V600E mutation. The FFPE ameloblastoma samples were independently submitted to index test and reference standard. Sensitivity and specificity measures, and positive and negative predictive values were calculated. Results: Fifty-four FFPE ameloblastoma samples were included. The sensitivity and specificity of IHC using the RM8 clone compared do Real-Time PCR for the detection of the BRAF V600E mutation in FFPE ameloblastoma samples was 1.00 (95%CI 0.90–1.00) and 0.46 (95%CI 0.21–0.73), respectively, and the diagnostic test accuracy was calculated as 85.18%. Conclusion: IHC using BRAF V600E-specific antibody (RM8 clone) showed extremely high sensitivity, but suboptimal specificity when compared with Real-Time PCR in the detection of BRAF V600E mutation in FPPE ameloblastoma samples.